Previsão da inflação no Boletim Focus: uma avaliação - Rocha, Marcus Vinicius Bonaldi Figueiredo (2010)
This work investigates and analyzes the differences between inflation’s annual rates and the forecasts by economic agents, for a year ahead. The inflation index examined, were the IPCA, IPA-M, IGP-M and IGP-DI. For each agents preview, for each index, we performed a statistical analysis and time series analysis, by ARIMA model. Through this model we understood the forecast errors of economic agents by the past values of forecast errors in the past, besides the stochastic terms.